Potret Kompetensi & Keterampilan Konselor di Era Society 5.0 - Muhyatun Muhyatun; Nailul Fauziyah (Al Irsyad : Jurnal Bimbingan Konseling Islam, 2022)
ABSTRACT In the era of society 5.0, humans become the center of the development of life and are expected to be able to balance the flow of progress that occurs in terms of social, economic, educational, religious, and cultural aspects through problem-solving skills that integrate two important things, namely cyberspace and physical space. In this era, technological transformation also demands the presence of new styles in all activities carried out by a person, including the exchange of ideas between individuals and groups. Therefore, humans and the professions they are involved in inevitably must rush to adjust their skills according to the existing conditions, including the counselor profession. Counselors must be able to take advantage of existing technology and increase their capacity, competence, and skills so that they can help counselees to solve various existing socio-cultural problems. This research was conducted to provide insight and description of the dynamics, trends, issues, and portraits of the competencies and skills of counselors needed in the era of society 5.0. This research uses the literature review method. Based on this research, it is known that in the era of society 5.0, to develop counseling services, a counselor must be able to synergize with the three main trends of current counseling, namely the shift in counseling issues (multicultural & social justice), artificial counselors (artificial intelligence) and Cybercounseling. The skills needed by counselors in the era of society 5.0 include competencies in the form of soft skills and hard skills.Keywords: Era Society 5.0, Skills, Counselor competence. ABSTRAKPada era society 5.0 manusia menjadi center dari perkembangan kehidupan dan diharapkan mampu menyeimbangkan arus kemajuan yang terjadi baik dari segi sosial, ekonomi, pendidikan, agama maupun budaya melalui kemampuan problem solving yang mengintegrasikan dua hal penting yaitu cyberspace dan physical space. Pada era ini, transformasi teknologi juga menuntut hadirnya gaya-gaya baru dalam seluruh kegiatan yang dilakukan oleh seseorang, termasuk kegiatan pertukaran gagasan baik antar individu maupun kelompok. Maka dari itu, manusia beserta profesi yang digelutinya mau tidak mau harus bergegas menyesuaikan keterampilan yang dimiliki sebagaimana kondisi yang ada, tidak terkecuali dengan profesi konselor. Konselor, harus dapat memanfaatkan teknologi yang ada serta meningkatkan kapasitas, kompetensi maupun keterampilan yang dimiliki supaya dapat membantu konseli menyelesaikan ragam persoalan sosiokultural yang ada. Penelitian ini dilakukan untuk memberikan wawasan dan gambaran mengenai dinamika, trend, isu dan potret mengenai kompetensi serta keterampilan konseloryang dibutuhkan di era society 5.0. Penelitian ini menggunakan metode kajian pustaka. Berdasarkan penelitian ini diketahui jika pada era society 5.0, dalam upaya pengembangan layanan konseling, seorang konselor harus bisa bersinergi dengan tiga trend utama konseling saat ini, yaitu pergeseran isu konseling (multikultural & keadilan sosial), konselor buatan (artificial intelligence) dan Cybercounseling. Adapun keterampilan yang dibutuhkan konselor di era society 5.0 meliputi kompetensi dalam bentuk soft-skill dan hard-skill. Kata Kunci: Era Society 5.0, Keterampilan, kompetensi Konselor.